Transformasi Rumah Tradisional Jawa di Jagalan Kotagede sebagai Penunjang Pariwisata - Wardiana, Indra Yuda; Rahmawati, Putri Annisa; Pratiwi, Wiwik Dwi; Herdian, Aldi (ATRIUM: Jurnal Arsitektur, 2025)
Title: Transformation of a Silversmith's House in the Selaka Group, Jagalan Village, Kotagede as a Tourism Support Based on the Governor's Decree Number 131/KEP/2023, Kotagede was designated as a Cultural Heritage Area because there are many sites, buildings, and cultural heritage structures due to their high historical and cultural value. This is reflected in the social life of the community, urban space, and architecture. Kotagede has experienced many physical changes in buildings causing the original characteristics to fade. Therefore, efforts are needed to preserve buildings so that they are not eroded by time, tourism development, and the demands of individual needs. The study aims to identify the forms and reasons for the transformation that occurred in Kotagede and to review the suitability with the principles of preserving traditional Javanese houses. The study used a qualitative method with a case study research approach. The study focused on the traditional house of the Selaka Kotagede group, a community that works together with the Arkom Indonesia Foundation and the AirAsia Foundation. The forms of change in Selaka silver craftsmen include the spatial structure system (organization, hierarchy, circulation, territory) and the physical system (building materials). Changes include the position of core, peripheral, and additional elements. The study found that the traditional house of Selaka Kotagede silver craftsmen experienced changes in the periphery and the addition of elements, but the core elements were maintained to maintain cultural identity. Thus, the preservation of cultural heritage buildings in Kotagede can be implemented by maintaining the core elements of traditional house buildings.